2021
DOI: 10.24875/ric.20000457
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Acute Myocardial Damage Secondary to Implantation of Electrodes for the Left Bundle Branch Area Pacing

Abstract: Background: Different from the traditional right ventricular pacing, the left bundle branch area pacing (LBBAP) is accomplished with deeper lead implantation and more attempts. However, myocardial damage is unclear in LBBAP. Objective: The objective of the study was to observe the change of troponin T and explore possible factors associated with greater myocardial damage in LBBAP. Methods: Patients with an indication for pacemaker implantation underwent attempts for LBBAP by transventricular septal method. Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In our research, we found that TnT increased observably after LBBAP. The results are similar to our previous reports [17]. Meanwhile, we observed there were no significant differences in TnT levels and coronary heart disease prevalence between the TWIs and non-TWIs groups at baseline.…”
Section: Twis During Lbbapsupporting
confidence: 92%
“…In our research, we found that TnT increased observably after LBBAP. The results are similar to our previous reports [17]. Meanwhile, we observed there were no significant differences in TnT levels and coronary heart disease prevalence between the TWIs and non-TWIs groups at baseline.…”
Section: Twis During Lbbapsupporting
confidence: 92%
“…The recent study about acute myocardial damage secondary to implantation of electrodes for the LBBaP found that the level of troponin T was significantly higher at 12 hours after LBBP surgery than that before operation (96.45 ± 11.07 vs 16.59 ± 1.84 ng/L, P < .001) and the number of attempts was an independent risk factor related to the myocardial damage by correlation and regression analysis. [ 28 ] However, it requires a further confirmation whether the myocardial damage of LBBaP is more serious than that of RVSP in prospective randomized clinical trials. At least, more attentions should be paid to the damage of ventricular septal coronary damage and the excessive number of attempts should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] In addition, myocardial damage deserves our attention in LBBP. The recent study [ 35 ] showed the number of attempts at lead position was an independent risk factor related to the myocardial damage, so excessive number of attempts should be avoided. It is worth noting that patients with intraventricular block, hypertrophic cardiomyopathy and ventricular septal infarction should not be treated with LBBP.…”
Section: Discussionmentioning
confidence: 99%